Genotypic differences in CC224, CC363, CC449 and CC446 of Moraxella catarrhalis isolates based on whole genome SNP, MLST and PFGE typing - Ya-Li Liu; Shu-Ying Yu; Xin-Miao Jia; Hai-Jian Zhou; Hong-Li Sun; Timothy Kudinha; Fanrong Kong; He-Ping Xu; Ying-Chun Xu (Elsevier, 2020)
Understanding the evolutionary path of M. catarrhalis from macrolide-susceptible to macrolide-resistant organism, is important for hindering macrolide resistance from propagation. Multilocus sequence typing (MLST), pulsed-field gel electrophoresis (PFGE) and whole genome SNP typing (WGST), as useful and practical typing tools, have both advantages and disadvantages.We studied the utility of these 3 typing methods, including the level of agreement, consistency and drawbacks, in characterizing M. catarrhalis clones and clonal complexes.We focused on four clonal complexes [CC224, CC363, CC449 (CCN10) and CC446 (CCN08)] and found that PFGE and WGST had a high level of agreement and a proper consistency of the same clone or very closely related clones, while MLST is less discriminatory for different clones. Furthermore, we also established an evolutionary distance cut-off value for "The same clone". Moreover, we detected macrolide-resistant M. catarrhalis in CC224, which had previously been considered as a macrolide-susceptible clonal complex. A higher number of isolates belonged to ST215 compared to ST446, implying that ST215 is more likely to be the primary founder. Our study also demonstrated that all the four clonal complexes belong to the M. catarrhalis lineage 1, which is considered to be related to increased virulence potential and serum resistance. We also observed that copB II was highly related to CC449 and LOS type B was mainly confined in CC224.In conclusion, these findings provide further insight into the evolutionary characteristics of M. catarrhalis.